Polarização induzida aplicada no estudo de ocorrencia de cobre localizada a nordeste de Caçapava do Sul (RS) - Moreira, César Augusto [UNESP]; Lopes, Syngra Machado [UNESP]; Schweig, Camila [UNESP] (My University, 2012)
Mineral research works are fundamentals for recognition and incorporation of new reserves. This paper present an integrated analysis of geologic and metallogenetics data, with results gotten from the application of the Induced Polarization geophysical method, in an copper ore occurrence, inserted in Camaquã sedimentary basin, situated in northeast of Caçapava do Sul city (RS). In area ocurr arkosean arenites average coarse, the intensely silicified and recrystallized, pertaining to Passo da Promessa Formation. The presence of azurita and malachite in breakings and high porosity zones of the host rock characterizes the mineral occurrence in surface, located in the crossing two fault families. The inversion models indicate the predominance of high chargeability in vulcanics tuff, rock of high porosity in relation to the andesites and metaconglomerates gifts in the area. The strong structural control of the mineral occurrence associated the high chargeability in volcanic tuff is indications of the hydrothermal fluid access by means of faults, until rocks with great porosity, where it occurred disseminations of copper sulfides in depth and carbonates in surface.

Trabalhos de pesquisa mineral são fundamentais para o reconhecimento e incorporação de novas reservas. Este trabalho apresenta uma análise integrada de dados geológicos e metalogenéticos, com resultados obtidos a partir da aplicação do método geofísico de Polarização Induzida, numa ocorrência mineralizada em cobre, inserida na bacia sedimentar do Camaquã, situada a nordeste da cidade de Caçapava do Sul (RS). Na área ocorrem arenitos arcoseano médio a grosseiro, intensamente silicificados e recristalizados, pertencentes à Formação Passo da Promessa. A presença de azurita e malaquita em fraturas e zonas de maior porosidade da rocha encaixante caracteriza a ocorrência mineral em superfície, localizada no cruzamento de duas famílias de falhas. Os modelos de inversão indicam o predomínio de alta cargabilidade em tufos vulcânicos, rocha de maior porosidade em relação aos andesitos e metaconglomerados também presentes na área. O forte controle estrutural da ocorrência mineral associado a valores de elevada cargabilidade em tufos vulcânicos são indícios do acesso de fluidos hidrotermais por meio de falhas, até rochas com grande porosidade, onde ocorreram disseminações de sulfetos de cobre em profundidade e carbonatos em superfície.
Induced polarization applied in study of copper ocurrence localized an northest of Caçapava do Sul (RS)
Keywords: Fault; Geophysics; Modeling; Ore; Sulfide; andesite; fault; geophysical method; host rock; hydrothermal fluid; integrated approach; metallogenesis; ore deposit; polarization; porosity; recrystallization; sedimentary basin; silicification; sulfide; tuff; Brazil; Cacapava do Sul; Rio Grande do Sul